Crack identification using piezoelectric testing on carbon steel pipe for transverse, longitudinal and hole defects with low excitation frequency - N. Abdalla, Ahmed; Ali, Kharudin; Koh Siaw Paw, Johnny; Kok Hen, Chong; Jian Ding, Tan; Sham Maizal, M; Izzat, M (International Journal of Engineering and Technology, 2018)
AC excitation signal is most widely used in Non Destructed Testing (NDT) devices for Piezoelectric Technique (PZT) method in an inspec-tion. This paper is presenting the application of piezoelectric with end to end method for defect identification for Carbon Steel Pipe (CSP) where the frequency is used around 1kHz until 6kHz for standard pipe, transverse defect pipe, longitudinal defect pipe and hole defect pipe. From here, the identification of defect signal by based on the signal pick value and different pick signal between ordinary pipe (without defect) and defects pipe are analysis. The result shows that the standard pipe will give the high amplitude of signal compare the defect pipe by based on the type of defect, size of defect and depth of defect. Findings from the comparative study, validate the application of piezoelec-tric show that the different amplitude of the signal is directly proportional with excitation signal frequency and through the experiment, the longitudinal defect is contributed the different high signal until 79.7% compared to the hole and transverse defect 74.4 %.